TURBULENT MIXING IN OMBAI STRAIT - Yulianto Suteja; Mulia Purba; Agus S. Atmadipoera (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Ombai Strait is one of the exit passages of Indonesian Throughflow (ITF) which conveys hotspot of strong internal tidal energy. Internal tide is the one of main energy which causes mixing processes in the oceans and could lead to changes in water mass characteristics. The purpose of this research was to estimate the turbulent mixing by using Thorpe analysis. Nine CTD cast were obtained for one tidal cycle (24 hours) in Ombai Strait. The results showed the average value of the turbulent mixing is 833.5 x 10-4 m2s-1, the highest found in deep homogeneous layer (2383.4x 10-4 m2s-1), followed by mixed surface layer (103.0 x 10-4 m2s-1) and thermocline (14.2 x 10-4 m2s-1). This Turbulent mixing value is much higher than the previous measurement in Indonesian Sea. This is presumably due to the strong internal tidal energy and its interaction with existing deep sill in Ombai Strait. Keywords: Indonesian throughflow (ITF), Ombai Strait, turbulent mixing